The effects of physical activity on adolescents’ depression: evidence from China - Chen, Hongmei; Liu, Meng; Zhao, Wenqing; Wei, Hanlin; Zhang, Ying; Li, Shunguo (Frontiers in Psychology, 2024)
Background: Depression is becoming a common threat to the mental health of Chinese adolescents .As an intermediate stage between being healthy and having depression, identifying factors influencing depressive may contribute to providing more options for the prevention and treatment of depression.The study aims to explore the effects of physical activity on adolescent depression, focusing on the times and hours of activity per week.The study used a cross-sectional dataset collected in Ruyang County, Henan Province in September 2022, including a sample of 5629 adolescents in 31 compulsory public schools in the county. We utilized Ordinary Least Squares (OLS) to analyze the impact of physical activity on adolescents' depression scores, and probit model to analyze the influence of physical activity on adolescents' depression. To examine whether there is a U-shaped relationship between physical activity and depression, we included the squared terms of times and hours of activity in models.The results showed that: (1) The times of physical activity significantly reduces Chinese adolescent depression. An increase in physical activity by one time per week is associated with a mean decrease of 0.354 points in depression scores (p<0.01). However, an increase of one time of physical activity per week is associated with an average 1% increase in the likelihood of experiencing depression(p<0.05), while the hours of physical activity was statistically insignificant. (2)Physical activity has a U-shaped (not linear) relationship with adolescent depression, with 7-8 times per week or 7-9 hours of physical activity per week being the optimal range.The study found that increasing the frequency of physical activity positively impacts adolescent depression, while increasing the hours does not show a significant association. Furthermore, a U-shaped relationship exists between times of activity, hours of activity, and adolescent depression, suggesting that moderate activity is optimal.